PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE - Sari, Fitri Nanda; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research studies the influence of financial performance to the stock return on the food andbeverages companies which are listed in Indonesia Stock Exchange (IDX) in the years of 2010-2012.This research is meant to find out the influence of financial performance to the stock return. Thepurposive sampling method has been used as the sample collection method and 13 of 16 companieswhich are listed in Indonesia Stock Exchange in the years of 2010-2012 have been selected as researchsamples. The dependent variable in the research is stock return variable, whereas Current Ratio, Debtto Equity Ratio, Return on Asset, and Total Asset Turnover variables are used as the independentvariables of the research. The multiple regressions analysis is used as the data analysis method. Theresult of the research shows that simultaneously Current Ratio, Debt to Equity Ratio, Return onAsset, Total Asset Turnover variables have significant influence to the stock return. Partially currentratio variable has significant influence to the stock return, meanwhile Debt to Equity Ratio, Returnon Assets, Total Asset Turnover does not have any significant influence to the stock return.Keywords: Current Ratio, Debt to Equity Ratio, Return on Asset, Total Asset Turnover and StockReturn.